PENERAPAN ALGORITMA A* PADA WEBGIS PENCARIAN RUTE TERPENDEK - Alzena Dona Sabilla; Ahmad Taufiq (Journal of Information System and Computer, 2022)
Geographic information systems have been able to solve routing problems such as TSP (Travelling Salesman Problems) or finding the closest route. GIS has developed a lot into GIS applications, both in the form of desktop, web, and mobile. This research develops a webGIS application that can provide a solution for tourists who have difficulty reaching a furniture showroom in Jepara City. The method used is the A* algorithm. The algorithm can calculate existing nodes through heuristic calculations. Data from google maps are converted into a grid form, then calculations are carried out. This research produces an alternative shortest route, while the accuracy of Google Maps road data affects the displayed route search.